Aspect bactériologique d’un poisson pélagique (Scomber japonicus (Houttuyn, 1782)) pêché dans la région de Mostaganem - Flih, Hayat; Ferhi, Hanane (My University, 2020)
The mackerel Scomber japonicus (Houttuyn, 1782) is an important source of animal protein for the populations. In order to evaluate the microbiological quality of this fish sold to consumers, a microbiological study was conducted on 13 samples of mackerel caught in the Mostaganem area. Research conducted at the Fisheries Laboratory of Mostaganem University has revealed a presence of germs impairing quality. Microbiological analyzes have shown that the quality of the mackerel samples is unsatisfactory in the following proportions: 2,39,109 germe / gram and a drop to 10,107 germe / gram for aerobic mesophilic bacteria and 30 germe / gram up to 1,240,103 germe / gram for total coliforms, 10 germe / gram up to 1.15 .103 germe / gram for faecal coliforms and 20 CFU / gram up to 2.40 .102 CFU / gram for yeast and 2 CFU / gram for mold. In addition, two of the mackerel samples analyzed were contaminated with sulphite reducing anaerobic germs. Salmonella spp. And Staphylococcus aureus were not detected.
Keywords: mackerel; Scomber japonicus; microbiological quality; Mostaganem.